Highly Efficient and Comprehensive Identification of Ethyl Methanesulfonate-Induced Mutations in Nicotiana tabacum L. by Whole-Genome and Whole-Exome Sequencing - Udagawa, Hisashi; Ichida, Hiroyuki; Takeuchi, Takanori; Abe, Tomoko; Takakura, Yoshimitsu (Frontiers in Plant Science, 2021)
Tobacco (Nicotiana tabacum L.) is a complex allotetraploid species with a large 4.5-Gb genome that carries two copies of each gene. In this study, we describe the development of a whole-exome sequencing (WES) procedure in tobacco and its application to characterize a test population of ethyl methanesulfonate (EMS)-induced mutations. A probe set covering 50.3-Mb protein coding regions was designed from a reference tobacco genome. The EMS-induced mutations in 19 individual M2 lines were analyzed using our mutation analysis pipeline optimized to minimize false positives/negatives. In the target regions, the on-target rate of WES was approximately 75%, and 61,146 mutations were detected in the 19 M2 lines. Most of the mutations (98.8%) were single nucleotide variants, and 95.6% of them were C/G to T/A transitions. The number of mutations detected in the target coding sequences by WES was 93.5% of the mutations detected by whole-genome sequencing (WGS). The amount of sequencing data necessary for efficient mutation detection was significantly lower in WES (11.2 Gb), which is only 6.2% of the required amount in WGS (180 Gb). Thus, WES was almost comparable to WGS in performance but is more cost effective. Therefore, the developed target exome sequencing procedure provides an efficient solution in the genome-wide analysis of tobacco, and could become a fundamental tool in high-throughput mutation identification processes.